2015
DOI: 10.1007/s00726-015-2079-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic study of urinary polyamines in rat exposed to 915 MHz radiofrequency identification signal

Abstract: Metabolomic analysis of urinary polyamines (PAs) from rat exposed to 915 MHz radiofrequency identification (RFID) signal for 8 h/day for 2 weeks was performed by gas chromatography-mass spectrometry as N-ethoxycarbonyl/N-pentafluoropropionyl derivatives. Large alterations in nine PA levels including four aliphatic and five acetylated PAs were monitored in sham-exposed and RFID-exposed groups. Total PA and urinary levels of N (1)-acetylputrescine, N (1)-acetylcadaverine, putrescine, cadaverine, N (1)-acetylsper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Also, 1 h of exposure to a 1,439‐MHz time‐division multiple access fields at a brain‐average SAR of 7.5 W/kg (peak SAR of 11 W/kg or whole‐body average SAR of 1.7 W/kg) did not alter the body temperature in rats, but such exposure at a brain‐average SAR of 25 W/kg (peak SAR of 39 W/kg or whole‐body average SAR of 5.7 W/kg) raised the body temperature by 2 °C [Yamaguchi et al, ]. However, in another study, exposure to an EMF at an average of 4 W/kg whole‐body SAR did not significantly alter the body temperature [Kim et al, ; Paik et al, ; Wyde et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, 1 h of exposure to a 1,439‐MHz time‐division multiple access fields at a brain‐average SAR of 7.5 W/kg (peak SAR of 11 W/kg or whole‐body average SAR of 1.7 W/kg) did not alter the body temperature in rats, but such exposure at a brain‐average SAR of 25 W/kg (peak SAR of 39 W/kg or whole‐body average SAR of 5.7 W/kg) raised the body temperature by 2 °C [Yamaguchi et al, ]. However, in another study, exposure to an EMF at an average of 4 W/kg whole‐body SAR did not significantly alter the body temperature [Kim et al, ; Paik et al, ; Wyde et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 333 studied the effect of 915 MHz RFID exposure in rats where no change in thyroid secretory function in connection with triiodothyronine (T3), thyroxine (T4), and thyroid-stimulating hormone (TSH) was observed in sham-exposed and RFID exposed rats. Paik et al 334 reported that 915 MHz RFID exposure alters urinary polyamines (PAs) in rats. The level of N 1 -acetylspermine was found to be 54% higher aer RFID exposure whereas it increased 17% in the sham group.…”
Section: Resultsmentioning
confidence: 99%
“…PA is being studied with a focus on cell growth, cell proliferation, protein, and nucleic acid synthesis by controlling its acetylation-deacetylation, according to changes in biochemical conditions [92][93][94]. Recently, studies on PA have focused on its role in a PA-mediated stress response signaling system and as a marker for monitoring and diagnosing various disease states [95][96][97]. Therefore, endogenous PA profile analysis is important for understanding biochemical changes post GHB exposure.…”
Section: Ghb-associated Metabolic Changes In Aa Oa and Polyamine (Pa)mentioning
confidence: 99%